The Correlation between Students’ Reading Speed and Their Reading Comprehension in Descriptive Text - Dewi, Risnawati; Mulyana, Agus; Nuraini, Hery; Purnawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2022)
The purpose of the research is to find out the correlation between students’ reading speed and their reading comprehension of descriptive text among the tenth-grade students of SMAN 14 Kabupaten Tangerang in the academic year 2018/2019. The population of this research is the whole students in tenth grade at SMAN 14 Kabupaten Tangerang. The writers chose 73 students as the sample of this research by using simple random sampling. In this research, the writers applied principles of the quantitative method with correlation form. The data was collected by using Reading Speed as variable X and Reading Comprehension as variable Y. The data is analyzed by using Pearson correlate and the result of it is 0.398. It means the result of r-xy (0.398) is higher than the r-table (0.329). So it can be concluded that there is a positive correlation between students’ reading speed and their reading comprehension among tenth-grade students of SMAN 14 Kabupaten Tangerang in academic years 2018/2019.